Indigenous Stewardship: Religious Praxis and “Unsettling” Settler Ecologies - Avalos, Natalie (Political theology, 2023)
Settler colonialism has been described as a structure, not an event, meaning it is sustained over time through discursive and material means. As settlers began to monopolize lands, new ecologies were built from Indigenous ones, transforming the landscape but also human relations with lands. I expand on Kyle Whyte’s concept of settler ecologies to understand these ecologies as drawing from a metaphysic, a Christian cosmo-logic of divine hierarchy that positions some humans as having ontological superiority over the natural world and other humans. I draw from decolonial, Indigenous, and settler colonial theory to explore how settler ecologies reterritorialize the land through racial-religious formations, what Aboriginal scholar, Aileen Moreton-Robinson calls the white possessive, and become naturalized in a modern context through secular, biopolitical discourses of development. I argue that these settler ecologies are “unsettled” through the sacred directive of stewardship movements that emerge from the unifying, intersubjective relations of ceremonial life.